In vitro inhibition of fungi causing postharvest green and blue mold of citrus fruits by agricultural by-products extract - Souza, Ricardo-Lima-de; Pérez-Gago, María B.; Palou, Lluís (2023)
Citrus are among the most important crops in the Mediterranean basin. Citrus fruit consumption has health benefits due to the content of vitamins and minerals. During postharvest storage, citrus fruits are susceptible to green and blue molds, caused by Penicillium digitatum (PD) and 95 Penicillium italicum (PI), respectively. To control these diseases, chemical fungicides are commonly used. However, many of them are reportedly harmful to humans and the environment. Agricultural by-products (ABP) are rich in a variety of bioactive compounds, such as (poly)phenols, essential oils, terpenoids, and alkaloids, which might have antifungal properties. Thus, the bioactive compounds of ABP could be a sustainable source of novel antifungal agents for citrus molds control. Moreover, the use of ABP contributes to the circular economy by valorizing value-added compounds. The aim of this work was to evaluate in vitro the inhibitory effect of extracts from ABP from Spain. Extracts from olive pomace (ALP), almond skin (AMS), and avocado seed (AVS) were tested against PD and PI. Extracts were obtained from lyophilized samples of each by-product by an ultrasound-assisted extraction procedure using a hydroalcoholic solution. The extracts were characterized by their total phenolic content (TPC) and total antioxidant capacity (TAC). The in vitro inhibitory activity of extracts was investigated using a microtiter assay employing a 96-well plate. In each well, 20 μL of extract, 150 μL of Potato Dextrose Broth (PDB) culture medium, and 30 μL of fungal inoculum containing 1.5x105 spores/mL were pipetted. Sterile water was used in controls instead of inoculum or extract to achieve a final volume of 300 μL. Finally, the plates were incubated in the dark at 25°C, and the optical density of each well was measured using a spectrophotometer at 600 nm every 24h for 4 days. The inhibitory activity of the extracts was calculated with respect to the control treatment (PDB without extract) on day 4. TPC was higher in the AVS extract (427.40 mg GAE/g DW), whereas AMS and ALP yielded lower values (32.79 mg GAE/g of DW and 12.21 mg GAE/g DW, respectively). Moreover, TAC was higher in the AMS extract (4.89 g AAE/L), followed by ALP (4.62 g AAE/L) and AVS (3.07 g AAE/L). In the in vitro assays, AMS and AVS extracts inhibited 100% of PD fungal growth, whereas ALP inhibited 81%. Regarding PI, AVS inhibited 100%, AMS 97%, and ALP only 55% of fungal growth. The results suggest that extracts with higher TPC and TAC had a more significant inhibitory effect against PD and PI. Therefore, in this work, the presence of (poly)phenols and antioxidants correlated with the antifungal activity of the ABP extracts. Moreover, AVS and AMS extracts have the potential to be used as a source of novel antifungal agents to control postharvest green and blue molds of citrus. Further studies should investigate the in vivo antifungal activity of the AVS and AMS extracts and their characterization by HPLC.